Legal Regulation of Interest Rates under the Loan Agreement, with the Participation of the Borrower – the Entity, under the Civil Law of Ukraine and Germany: A Comparative Characteristic - BABASKIN, Anatoly Yu.; PARKHOMENKO, Natalya M. (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019DO - 10.14505/jarle.v10.3(41).01, 2019)
The relevance of the study is due to the fact that there is a growing need to study civil law and its practice in Ukraine and the most economically developed countries of the European Union. The purpose of the study is to conduct a comparative analysis of the legal regulation of interest rates under the loan agreement, with the participation of the entity, in the civil legislation of Ukraine and Germany, in order to identify similar features, differences, deficiencies in their legal regulation, and identify possible areas for improvement of the rules of civil law of Ukraine. The article investigates the legal nature of interest rates in credit relations, legal regulation of types of interest rates, bases of accrual of interest on a loan, restriction of freedom to set the amount of interest rate on a loan agreement, the order of payment of interest on a loan, etc. In the course of the research, similar features and differences in the legal regulation of interest rates in the credit agreement in the legislation of Ukraine and Germany were identified, deficiencies and possible directions of improvement of the civil legislation of Ukraine in the specified field were identified.